Sistem Pendataan Peserta PKH Lolos Jalur Seleksi Perguruan Tinggi Berbasis Website Pada Lembaga Mitra Gerakan Ayo Kuliah Lampung - Edo Laksana Widodo; Rendy Lutfi Prabowo; Wartariyus Wartariyus; M. Iqbal Parabi (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The Bakrie Center Foundation is a charitable organization established in 2010, dedicated to nurturing emerging leaders in Indonesia. Its vision is to identify and cultivate leaders across all strata of society throughout the Indonesian archipelago, with a mission to bolster their capabilities and foster a talent pool that will ultimately stimulate national development and economic growth. In the 6th edition of the Campus Leader Program, the Bakrie Center Foundation collaborated with partner institutions as part of the